Mannose‐binding lectin gene polymorphism in relation to periodontal infection. (14th September 2016) - Liukkonen, A.; He, Q.; Gürsoy, U. K.; Pussinen, P. J.; Gröndahl‐Yli‐Hannuksela, K.; Liukkonen, J.; Sorsa, T.; Suominen, A. L.; Huumonen, S.; Könönen, E.
Abstract : Background and Objective: Mannose‐binding lectin (MBL) plays an important role in innate immunity. MBL deficiency is usually caused by mutations in exon 1 of the MBL structural gene ( MBL2 ). Our aim was to investigate MBL2 polymorphisms and their relation to salivary levels of periodontal inflammatory/tissue destruction markers and two major periodontitis‐associated bacteria. Material and Methods: Salivary samples from 222 subjects were available for genotyping by pyrosequencing. The subjects between 40 and 60 years of age and having a minimum of 20 teeth were divided into three periodontal groups: 80 had generalized periodontitis, 65 had localized periodontitis and 77 were periodontitis‐free. A comparison between their MBL2 genotypes and salivary detection rates and levels of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis as well as interleukin ‐1β, matrix metalloproteinase ‐8, and tissue inhibitor of matrix metalloproteinase (TIMP)‐1 was performed. Results: The frequencies of the MBL2 wild‐type (A/A), heterozygote variants (A/O) and homozygote variants (O/O) were 69.4%, 26.6% and 4%, respectively. In A. actinomycetemcomitans ‐positive subjects having homozygote or heterozygote MBL2 variants, the salivary concentrations of IL‐1β ( p = 0.010) were elevated and those of TIMP‐1 ( p = 0.001) were decreased. In addition their matrix metalloproteinase ‐8/TIMP‐1 ratio was higher ( p < 0.001) and they had more pocket teeth ( p = 0.012) than subjects negative for A. actinomycetemcomitans . Conclusion: Our findings indicate that the carriage of A. actinomycetemcomitans may facilitate extended periodontal inflammation and destruction in subjects with a variant form of human MBL2 .